2005
DOI: 10.1007/s00125-005-1715-5
|View full text |Cite
|
Sign up to set email alerts
|

The risk of venous thromboembolism is markedly elevated in patients with diabetes

Abstract: Aims/hypothesis: Diabetes mellitus is associated with several changes in coagulation and fibrinolysis that may lead to a thrombogenic propensity. However, it is not known whether these perturbations actually cause increased risk of venous thromboembolism. Methods: In a retrospective population-based study we evaluated the medical records of all 302 adult patients who were admitted to the Umeå University Hospital with verified deep vein thrombosis or pulmonary embolism during the years 1997 to 1999. The patient… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

8
159
2
9

Year Published

2006
2006
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 194 publications
(178 citation statements)
references
References 18 publications
8
159
2
9
Order By: Relevance
“…[36][37][38][39] Arterial hypertension and diabetes have also been found to be associated with VTE. 40,41 We were able to measure hs-CRP, fibrinogen and factor VIII activity in our study and these parameters were significantly elevated in the subgroup of individuals with the metabolic syndrome, which is concordant with previously reported data. 16, 21-23, 30, 31 People with the metabolic syndrome frequently have a pro-inflammatory state, as shown by increased acute-phase reactants (e.g., CRP, fibrinogen), 30,31 and also a prothrombotic state due to elevated levels of fibrinogen, PAI-1, and clotting factors.…”
supporting
confidence: 92%
“…[36][37][38][39] Arterial hypertension and diabetes have also been found to be associated with VTE. 40,41 We were able to measure hs-CRP, fibrinogen and factor VIII activity in our study and these parameters were significantly elevated in the subgroup of individuals with the metabolic syndrome, which is concordant with previously reported data. 16, 21-23, 30, 31 People with the metabolic syndrome frequently have a pro-inflammatory state, as shown by increased acute-phase reactants (e.g., CRP, fibrinogen), 30,31 and also a prothrombotic state due to elevated levels of fibrinogen, PAI-1, and clotting factors.…”
supporting
confidence: 92%
“…This observation was not surprising since the risk of VTE is increased in diabetic patients [11]. Other features of endocrinal disturbance, such as obesity and dyslipidemia, might be risk factors of DVT; however, a recent study concluded that symptoms of metabolic syndrome were not clinically important risk factors for VTE [12].…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, the increased incidence of VTE in patients with risk factors for arterial cardiovascular events points too to a common pathogenesis (6). Indeed, a number of studies, with different design and in various clinical settings, have shown an increased risk of VTE associated with most of the classic or novel risk factor for ischaemic cardiovascular disease (7)(8)(9)(10)(11)(12)(13)(14)(15)(16)(17)(18)(19)(20)(21)(22) (ǠTable 1).…”
Section: The Association Between Venous and Arterial Thrombosismentioning
confidence: 99%